2023
DOI: 10.1093/bjs/znad022
|View full text |Cite
|
Sign up to set email alerts
|

Oncological surgery follow-up and quality of life: meta-analysis

Abstract: Background Previous trials found that more intensive postoperative surveillance schedules did not improve survival. Oncological follow-up also provides an opportunity to address psychological issues (for example anxiety, depression, and fear of recurrence). This systematic review assessed the impact of a less intensive surveillance strategy on health-related quality of life (HRQoL), emotional well-being, and patient satisfaction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The review valuably consolidates evidence suggesting less-intensive follow-up strategies after oncological surgery do not adversely impact health-related quality of life (HRQoL), emotional well-being or patient satisfaction 1 . However, some elements merit closer consideration.…”
mentioning
confidence: 54%
“…The review valuably consolidates evidence suggesting less-intensive follow-up strategies after oncological surgery do not adversely impact health-related quality of life (HRQoL), emotional well-being or patient satisfaction 1 . However, some elements merit closer consideration.…”
mentioning
confidence: 54%
“…Its presence appears to be associated with reduced quality of life 21 . A recent study 22 evaluating health-related quality of life during oncological follow-up after surgery found that less intensive surveillance does not diminish emotional well-being or patient satisfaction. Taken together, the disadvantages of routine follow-up for detecting disease recurrence in patients with a non-high-risk GIST may outweigh the potential benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the detection of disease recurrence, follow-up contributes to psychological support and surveillance of postoperative complaints. However, less intensive follow-up has no negative influence on health-related quality of life (HRQoL) 6. Besides the lacking survival and HRQoL benefit, there are other reasons to revisit current follow-up practice in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…However, less intensive follow-up has no negative influence on health-related quality of life (HRQoL). 6 Besides the lacking survival and HRQoL benefit, there are other reasons to revisit current follow-up practice in patients with CRC. Frequent hospital visits have significant impact on patients’ lives, as follow-up visitations evoke distress around the time of visits.…”
Section: Introductionmentioning
confidence: 99%